NKp46 expression on NK cells as a prognostic and predictive biomarker for response to allo-SCT in patients with AML. (2nd December 2017) - Chretien, Anne-Sophie; Devillier, Raynier; Fauriat, Cyril; Orlanducci, Florence; Harbi, Samia; Le Roy, Aude; Rey, Jérôme; Bouvier Borg, Gaelle; Gautherot, Emmanuel; Hamel, Jean-François; Ifrah, Norbert; Lacombe, Catherine; et al.
ABSTRACT: NKp46 is a major determinant of natural killer (NK) cell function and it is implicated in tumor immune surveillance in acute myeloid leukemia (AML). The purpose of this study was to investigate the prognostic significance of NKp46 expression in an independent cohort of patients with AML, and to investigate the impact of NKp46 on clinical outcome after allogeneic stem cell transplantation (allo-SCT). NKp46 expression was assessed at diagnosis on NK cells by flow cytometry (N = 180 patients). Clinical outcome was evaluated with regard to NKp46 expression. Patients with NKp46 high phenotype at diagnosis had better progression-free survival (PFS) and overall survival (OS) than patients with NKp46 low phenotype (74.3% vs. 46.6%, p = 0.014; 82.6% vs. 57.1%, p = 0.010, respectively). In multivariate analysis, high NKp46 was an independent factor for improved OS (HR = 0.409, p = 0.010) and PFS (HR = 0.335, p = 0.011). Subgroup analysis revealed that allo-SCT had a favorable impact on PFS in patients with NKp46 high phenotype ( p = 0.025). By contrast, allo-SCT did not impact PFS in patients with low NKp46 expression ( p = 0.303). In conclusion, we validate the prognostic value of NKp46 expression at diagnosis in AML. However, the prognostic value of NKp46 expression is limited to patients treated with allo-SCT, thus suggesting that NKp46 status may be predictive for allo-SCT responsiveness.